Scrutiny and Study of Tea Production - Zahiryan, Rohullah (Journal of Natural Sciences – Kabul University, 2020)
Tea is the second most consumed beverage after water due to its health and cultural properties. It is brewed from the leaves of Camellia sinensis L. (Theaceae family), the same species from which white, oolong, black, and green teas are derived. The various types of tea are classified based on their processing methods and the oxidation and fermentation levels, which influence their taste and aroma profiles. Green tea is minimally oxidized and non-fermented. Green teas are most often sourced from the sinensis variety of the tea plant, while black teas are typically derived from the assamica variety. China is the center of green tea production, while India is one of the largest tea-producing, exporting, and consuming countries. Today, green tea is produced in over 20 countries across tropical, subtropical, and temperate regions.